PENERAPAN METODE PENELITIAN DI SEKOLAH TINGGI AGAMA ISLAM - Aulia Rahman (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
In carrying out the task of education, universities become a place to develop, confirm and formulate knowledge that has been obtained from previous levels of education. In its duty to carry out research, universities require teaching staff to conduct research and all matters related to research. Problems in research in universities are not only from research methods but can be from several sides such as limited resources, limited time, honesty and ethical problems, and research discontinuity. This article would like to describe the types of research methods used in students' final assignments on Islamic college campuses. In this research, researchers used qualitative methods with a case study approach at the Mandailing Natal State Islamic High School. The analysis used is the analysis of descriptions and literature reviews with data sourced from thesis writing manuals used by research cases and literature related to the research focus. Data validation techniques use source triangulation by comparing between information found. The results of this research are the application of research methods at the Mandailing Natal State Islamic College are correlational research, experimental and comparative causal research, action research, descriptive and historical research, literature research, evaluation research, development research, content analysis research, qualitative research, quantitative research, character thought research, and mixed research.